PENDAMPINGAN KEGIATAN OUTBOUND DALAM MENSTIMULASI PERKEMBANGAN FISIK MOTORIK ANAK USIA DINI - Muzakki; Nor Ma'rifah; Annisa Rahmasari; Devi Oktavia; Isnawati (JP2N : Jurnal Pengembangan Dan Pengabdian Nusantara, 2025)
Early childhood development is something that is very important for children. This can be stimulated through a series of games that can support aspects of development. One aspect that must be developed in early childhood is the physical motor aspect related to fine motor skills and gross motor skills. 6 types of outbound game activities, namely 1) Moving the flag to the bottle, 2) Blowing the ping pong ball on the water, 3) Hula Hoop Relay, 4) Putting the ping pong ball into the glass through the head, 5) Relay ping-pong balls using spoons, 6) Obstacle course. This community service activity is carried out using the service learning method. The target for this activity is 20 students at RA Al-Musafirin Palangk Raya. The results of this activity are that children can demonstrate the game well even though they still need assistance. Therefore, there is a need for more varied stimulation activities that can develop children's fine and gross motor skills.